Sharing experience in the framework of the project "English for Universities" (objectives and outcomes of training) - Garmash, Sergii; Sadkovska, V. A. (Херсонський державний університет, 2017)
This article is devoted to the new approaches in solving of the problems arisen during training process of learning English for specific purposes. As the title implies the article describes essentials, objectives and outcomes of this process. A detailed analysis of course objectives is given in the article. It is specially noted the transformational change in the level of English among both university teaching staff and students, urgent of this change in the epoch of globalization as nowadays globalization defines the modern world. Just the English language for specific purposes may be considered not only as a means of communication for specific group combined with the particular sphere of activities.

У статті досліджуються нові підходи у вирішенні проблем, які виникають у процесі вивчення англійської мови для спеціальних цілей. Відповідно до назви в статті описуються цілі і детально аналізуються результати цього процесу. Особливо відмічається трансформаційна зміна в рівні володіння англійською мовою як серед викладацького складу, так і серед студентів; важливість таких змін у період глобалізації, яка визначає сучасний світ. Саме англійська мова для спеціальних цілей може розглядатися як засіб вдалої комунікації в специфічній сфері діяльності.
Поширення досвіду в рамках проекту "Англійська мова для університетів" (цілі та результати навчання)
Keywords: ESP; British Council; course objectives; training process; transformational change; globalization; мова англійська; Британська Рада; процес навчальний; зміни трансформаційні; глобалізація